Legal Protection Efforts Against Domestic Violence Victims - Nurul Busyro (The International Journal of Politics and Sociology Research, 2022)
This study aims to determine Legal Protection Efforts Against Victims of Domestic Violence. The author uses sociological and victimological juridical-normative research methods. The results of this study are regulations that regulate acts of domestic violence that occurred in Sleman Regency, Special Region of Yogyakarta, namely at the Police level, at the Prosecutor's Office level and at the Court level, the legal basis used to ensnare perpetrators of domestic violence, namely those regulated in the Criminal Code (KUHP) Article 351 paragraph (1) in conjunction with Article 356 1 of the Criminal Code and/or in Article 44 paragraph (1) of the Law Number 23 of 2004 concerning the Elimination of Domestic Violence. The practice of law enforcement officials in cases of domestic violence in Sleman Regency, Special Region of Yogyakarta, is focused on the process of handling cases. There are 3 (three) criminal case examination processes, namely at the Police, Prosecutor and Court levels. Legal protection efforts are viewed from the perspective of law enforcement officials, namely the Police (Investigators), Public Prosecutors and Judges in rendering court decisions. Obstacles in providing legal protection for victims of domestic violence, at the level of the Police, Prosecutor's Office and at the Court level. Attorney and Court level. Legal protection efforts are viewed from the perspective of law enforcement officials, namely the Police (Investigators), Public Prosecutors and Judges in rendering court decisions. Obstacles in providing legal protection for victims of domestic violence, at the level of the Police, Prosecutor's Office and at the Court level. Attorney and Court level. Legal protection efforts are viewed from the perspective of law enforcement officials, namely the Police (Investigators), Public Prosecutors and Judges in rendering court decisions. Obstacles in providing legal protection for victims of domestic violence, at the level of the Police, Prosecutor's Office and at the Court level.